2013
DOI: 10.1097/mej.0b013e328357a6dd
|View full text |Cite
|
Sign up to set email alerts
|

Effective strategy for improving instructions for analgesic use in the emergency department

Abstract: Pain is a common presenting complaint of emergency department patients. Providing instructions that can be easily recalled by patients is an important step in enabling patients to manage their pain following discharge. The effect of the introduction of written discharge instructions for pain medication on patients' recall of instructions was evaluated in this study. A patient-control study within a prospective follow-up study was performed. In the first phase, no written discharge instructions were available. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…annemergmed.com). 5,25,26,33,34 Nonetheless, several studies showed a wide range of incorrect recall in at least one domain, varying from 23% to 92%. 6,27,29,32,37,39 Four studies specifically investigated elderly patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…annemergmed.com). 5,25,26,33,34 Nonetheless, several studies showed a wide range of incorrect recall in at least one domain, varying from 23% to 92%. 6,27,29,32,37,39 Four studies specifically investigated elderly patients.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have shown deficits in comprehension of discharge instruction. [4][5][6] For example, Engel et al 6 showed that a mere 13% of patients understood each of the 4 major domains of discharge instructions (diagnosis and cause, care given in the ED, care after the ED visit, and instructions on when to return to the ED). 6 Various studies have investigated patient education with a range of communication tools, and their results suggest that type of communication may influence correct recall of patients.…”
Section: How This Is Relevant To Clinical Practicementioning
confidence: 99%
“…An important intervention that continues to hold the promise of reducing OPR misuse and diversion is targeted patient education about the appropriate and safe use of OPRs. Prior research has demonstrated that patients are more likely to understand how to correctly take their medications if provided with written instructions in addition to verbal explanation prior to discharge, with individually tailored instructions recommended as a particularly effective strategy . Further, a recent randomized control trial by McCarthy et al involving 210 patients (median age 43 years) at an urban academic ED demonstrated that implementing a targeted educational intervention to patients discharged from the ED with OPRs improved patients’ understanding of their medication's side effects and resulted in fewer reports of driving within 6 h of taking the medication.…”
Section: Discussionmentioning
confidence: 99%
“…4 5 Many studies have demonstrated that patients often leave the ED unprepared because of comprehension deficits in key information domains such as the diagnosis and cause, ED treatment, post-ED care and return precautions. [6][7][8][9][10] The results from a cross-sectional analysis demonstrated, for example, that three out of four patients were unable to recall important information for at least one of these domains. 6 Furthermore, patients may not recognise when they have limited understanding, 6 11 suggesting an inability to seek help when needed.…”
Section: Introductionmentioning
confidence: 99%